Potential application of sludge produced from coal mine drainage treatment for removing Zn(II) in an aqueous phase - Cui, M.; Jang, M.; Cho, S.H.; Khim, J. (2011)
Various analyses of physico-chemical characteristics and batch tests were conducted with the sludge obtained from a full-scale electrolysis facility for treating coal mine drainage in order to find the applicability of sludge as a material for removing Zn(II) in an aqueous phase. The physico-chemical analysis results indicated that coal mine drainage sludge (CMDS) had a high specific surface area and also satisfied the standard of toxicity characteristic leaching procedure (TCLP) because the extracted concentrations of certain toxic elements such as Pb, Cu, As, Hg, Zn, and Ni were much less than their regulatory limits. The results of X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) showed that the CMDS mainly consists of goethite (70) and calcite (30) as a weight basis. However, the zeta potential analysis represented that the CMDS had a lower isoelectric point of pH (pHIEP) than that of goethite or calcite. This might have been caused by the complexation of negatively charged anions, especially sulfate, which usually exists with a high concentration in coal mine drainage. The results of Fourier transform infrared (FT-IR) spectrometry analysis revealed that Zn(II) was dominantly removed as a form of precipitation by calcite, such as smithsonite ZnCO3 or hydrozincite Zn5(CO3)2(OH)6. Recycling sludge, originally a waste material, for the removal process of Zn(II), as well as other heavy metals, could be beneficial due to its high and speedy removal capability and low economic costs. Â© 2010 Springer Science+Business Media B.V.